DETERMINANTS OF SAVINGS BEHAVIOR AMONG INDONESIAN MIGRANT WORKERS FROM KULON PROGO, YOGYAKARTA - Gatri, Betasari Ulfa; Mafruhah, Izza (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research aims to determine the influence of age, length of work, formal education, income, remittances, number of dependents, marital status, determinants of money use, employment sector, informal education, and gender on the savings of Indonesian Migrant Workers (PMI) both partially and simultaneously. This quantitative study uses primary data collected through interviews and questionnaires, with a sample of 100 post-placement PMI individuals from Kulon Progo Regency. Multiple linear regression analysis was employed to evaluate the data. The t-test results indicate that age and income have a positive and significant effect on PMI savings, whereas length of work and remittances show a negative and significant impact. Formal education and the number of dependents exhibit a positive but insignificant relationship with PMI savings. Furthermore, the dummy variables for marital status, determinants of money use, employment sector, informal education, and gender do not significantly affect PMI savings, indicating no difference between the dummy categories. The F test reveals that all variables combined—age, length of work, formal education, income, remittances, number of dependents, marital status, determinants of money use, employment sector, informal education, and gender—significantly impact PMI savings.